Percutaneous Cholecystostomy is a Reasonable Alternative for the Treatment of Acute Cholecystitis in Critically Ill Patients: a Single Center Analysis - Ignatavicius, Povilas; Kiudelis, Mindaugas; Dekeryte, Inga; Mikuckyte, Deimante; Sasnauskaite, Jolita; Lukasevic, Karina; Barauskas, Giedrius (Lietuvos chirurgija, 2019)
Background / objective. Laparoscopic cholecystectomy is a safe procedure and the treatment of choice for acute cholecystitis. As an alternative treatment option in critically ill patients percutaneous cholecystostomy (PC) is performed.Methods. Retrospective review of patients who had undergone PC from 2008 to 2017 at the Department of Surgery, Hospital of Lithuanian University of Health Sciences Kaunas Clinics. Patients were reviewed for demographic features, laboratory tests, ASA class, complications, outcomes, hospital stay and mortality rate.Results. Fifty-four patients were included in the study. Forty patients (74%) were ASA III and ten patients (18.5%) – ASA IV. Statistically significant decrease in white blood cell count (from 14.26±6.61 to 8.65±5.15) and C-reactive protein level (from 226.22±106.60 to 51.91±63.70) following PC was observed. The median hospital stay was 13.06 (range 2–68) days and 30-day mortality rate 13%. There were no deaths directly related to procedure. For eleven patients (20.4%) delayed cholecystectomy was scheduled.Conclusions. PC is a reasonable treatment option for high-risk patients with acute cholecystitis and co-morbidities. It can be used as a temporizing treatment option or as a definitive treatment with a low number of delayed cholecystectomies.
Keywords: acute cholecystitis; cholecystostomy; cholecystectomy; laparoscopic cholecystectomy